Report of the ACBS Task Force on the Strategies and Tactics of Contextual Behavioral Science Research - Hayes, Steven C.; Merwin, Rhonda M.; McHugh, Louise McHugh; Sandoz, Emily K.; A-Tjak, Jacqueline G. L.; Ruiz, Francisco J.; Barnes-Holmes, Dermot; Bricker, Jonathan B.; Ciarrochi, Joseph; Dixon, Mark R.; Fung, Kenneth Po-Lun; Gloster, Andrew T.; et al. (Perspectivas em Análise do Comportamento, 2025)
Throughout its history the strategy and tactics of contextual behavioral science (CBS) research have had distinctive features as compared to traditional behavioral science approaches. Continued progress in CBS research can be facilitated by greater clarity about how its strategy and tactics can be brought to bear on current challenges. The present white paper is the result of a 2 1/2-year long process designed to foster consensus among representative producers and consumers of CBS research about the best strategic pathway forward. The Task Force agreed that CBS research should be multilevel, process-based, multidimensional, prosocial, and pragmatic, and provided 33 recommendations to the CBS community arranged across these characteristics. In effect, this report provides a detailed research agenda designed to maximize the impact of CBS as a field. Scientists and practitioners are encouraged to mount this ambitious agenda.